Study on the thermal properties of the grafted product of maleic anhydride onto clylized natural rubber by using thermogravimetric method - M. Said Siregar; Dian Arsita Fitri; Muhammad Iqbal Nusa; Desi Ardilla; Masyura M.D; Asmarasari Nasution; Eddiyanto Eddiyanto (Pascasarjana Universitas Negeri Medan, 2022)
This study aims to investigate the thermal properties of grafted products of maleic anhydride onto cyclized natural rubber. The grafting was carried out in the melt phase at an internal mixer of 150 oC and a rotor speed of 80 rpm. A total of 16 phr maleic anhydride was reacted with cyclized natural rubber in the present and absence of divinylbenzene comonomer with various mole ratios: 0.5, 1, and 2. The grafted products were characterized by the thermogravimetric method to investigate their thermal properties. Based on the results of the thermogravimetric analysis, it was shown that the sample increased its thermal stability. The sample decomposes at a higher temperature with the increasing mole ratio of divinylbenzene added. The grafted product with 16 phr maleic anhydride decomposed at 489.41 oC. Then, the graft product samples with the addition of 0.5, 1, and the 2-mole ratio of divinylbenzene comonomers decomposed at: 501.62 oC, 514.39 oC, and 520.82 oC, respectively.Keywords:Cyclized natural rubber, Divinylbenzene, Maleic anhydride, Thermamogravimetric